2015
DOI: 10.4314/gjpas.v21i2.3
|View full text |Cite
|
Sign up to set email alerts
|

<i>In vitro</i> screening of selected herbicides on rhizosphere mycoflora from yellow pepper (<i>Capsicum annum</i> L var. Nsukka yellow) seedlings in Nsukka, Enugu state, Nigeria

Abstract: In vitro screening of five selected herbicides at different concentrations on rhizosphere mycoflora from yellow pepper (capsicum annum L var. Nsukka yellow) seedlings at Nsukka were investigated. The herbicides employed for this study were Paraquat, Glyphosate, Primextra, Atrazine and Linuron. The isolated rhizosphere mycoflora organisms screened were Rhizopus stolonifer (Ehren ex. Fr) Lind, Trichoderma harmatum Bain aggr; Aspergillus niger Van Tiegh; Sclerotium rolfsii Sacc; Penicillium sp; Alternaria sp; Fus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
3
0
0
Order By: Relevance
“…The results of this present experiment also indicated that application various herbicides evinced high potency on inhibiting growth of fungi. The inhibition of mycelial growth of rhizosphere and rhizoplane fungi by herbicides (Glyphosate, Paraquat, Atrazine and Linuron) applied was consistent with previous studies [64][65][66].…”
Section: Microbial Populationsupporting
confidence: 92%
“…The results of this present experiment also indicated that application various herbicides evinced high potency on inhibiting growth of fungi. The inhibition of mycelial growth of rhizosphere and rhizoplane fungi by herbicides (Glyphosate, Paraquat, Atrazine and Linuron) applied was consistent with previous studies [64][65][66].…”
Section: Microbial Populationsupporting
confidence: 92%
“…The inhibition of fungal mycelial growth by herbicide application was consistent with the ndings of previous studies [102][103]. Similarly, Eze [104] reported that glyphosate, paraquat, atrazine and linuron were more effective at inhibiting the mycelial growth of all the rhizoplane fungi screened than was primextra.…”
Section: Microbial Populationsupporting
confidence: 89%
“…The inhibition of mycelial growth of fungi by herbicide application was consistent with previous studies [102][103]. Similarly, Eze [104] had found that Glyphosate, Paraquat, Atrazine and Linuron were more effective on inhibiting the mycelial growth of all the rhizoplane fungi screened than Primextra.…”
Section: Microbial Populationsupporting
confidence: 88%